A synopsis of Agnetina (Plecoptera: Perlidae) from Vietnam - Li, Weihai; Wang, Guoquan (Zootaxa, 2012)
A new species of the genus Agnetina are described from northern Vietnam, A. vietnamica sp. n. Its taxonomic relationships with the related species are discussed. The holotype is deposited in the Henan Institute of Science and Technology, China.